ChemInform Abstract: 25th Anniversary Article: Colloidal Quantum Dot Materials and Devices: A Quarter‐Century of Advances. Issue 48 (26th November 2013) - Kim, Jin Young; Voznyy, Oleksandr; Zhitomirsky, David; Sargent, Edward H.
Abstract Review: 216 refs.